1993
DOI: 10.1002/jez.1402670108
|View full text |Cite
|
Sign up to set email alerts
|

Fiber growth initiation in hair follicles of goats treated with melatonin

Abstract: The sequence of structural changes in goat hair follicles was investigated using melatonin implants to advance and synchronize spring hair growth. Ten pasture fed cashmere wethers each received a controlled release formulation of 70 mg of melatonin on September 1 1989, and showed plasma melatonin elevated above physiological levels over 14 days post-treatment (914 +/- 154 pg/ml [mean +/- SEM] on day 14). In ten untreated animals, daytime plasma melatonin was 19.9 +/- 4.7 pg/ml. Histological examination of skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 16 publications
4
38
0
Order By: Relevance
“…Thus, animals fed with a melatonin-supplemented diet showed an increased rate of hair growth in springtime, the period of change from the winter coat to summer fur ( 51 ). The results were independently confirmed in other experimental models ( 52,53 ). The fur growth may be mediated by melatonin binding sites/receptors, because these were identified in the rodent skin ( 19,54,55 ).…”
Section: Phenotypic Effects Of Melatoninsupporting
confidence: 78%
“…Thus, animals fed with a melatonin-supplemented diet showed an increased rate of hair growth in springtime, the period of change from the winter coat to summer fur ( 51 ). The results were independently confirmed in other experimental models ( 52,53 ). The fur growth may be mediated by melatonin binding sites/receptors, because these were identified in the rodent skin ( 19,54,55 ).…”
Section: Phenotypic Effects Of Melatoninsupporting
confidence: 78%
“…This indicates that, in the New Zealand cashmere goat, there is a more distinct autumn moult, as in the mink (AUain et al 1981). In accordance, Nixon et al, (1993) observed an induction of proanagen, the first stage of the initiation of activity, in response to a smaU decrease in circulating prolactin concentration, foUowing melatonin administration in the spring. Initially, this appears to be contradictory to the results presented above; however, this response to a decrease in prolactin concentration can be likened to the induction of winter coat growth, in the autumn, as demonstrated in the mink (Allain et al 1981).…”
supporting
confidence: 78%
“…Telogen foUicles were identified by the lack of a distinct inner root sheath, and a darker staining of the nuclei in the outer root sheath which appear to point inwards. For detaUed descriptions of the sequence of structural changes in the hair follicle cycle see Nixon et al (1993), Chase (1958) …”
Section: Histologymentioning
confidence: 99%
“…Fixed samples were then processed overnight through graded concentrations of ethanol in an automatic tissue processor, embedded in paraffin polymer wax blocks, and sectioned at 7 μm. Section ribbons were floated in a water bath at 38-40°C and captured on glass slides that were coated with an albumin solution and stained by the Sacpic method [23] to determine the follicle characteristics.…”
Section: Sample Collections and Preparationsmentioning
confidence: 99%